Supramolecular porous frameworks of two Ni(II) coordination polymers with varying structures, porosities, and magnetic properties. (1st October 2022) - Zhou, Yue; Zhang, Yang-Lu; Zhang, Qian; Yang, Shun-Yi; Wei, Xiao-Qin; Tian, Zhengfang; Shao, Dong
Graphical abstract: Two nickel(II) supramolecular porous frameworks sustained by hydrogen bonding and π–π interactions were reported to show different crystal colour, supramolecular architectures, gas adsorption capacity, and magnetic anisotropy. Abstract: Based on a simple benzimidazole derivative and nickel nitrate, two nickel(II) based supramolecular three-dimensional (3D) porous solids, namely {[Ni(Hbic)2 (OH2 )2 ]·H2 O}n (1) and {[Ni(Hbic)2 (OH2 )]·2CH3 OH}n (2 ) (H2 bic = 1H-benzimidazole-5-carboxylic acid), were synthesized and characterized. Single crystal X-ray diffraction experiments revealed that compound 1 is a 1D coordination polymer with a linear chain structure while 2 is a 2D metal–organic framework (MOF) with a honeycomb network structure. Interestingly, the coordination chains in 1 and layers in 2 can form stable supramolecular 3D porous frameworks sustained by hydrogen bonding interactions and intermolecular π–π interactions. The distinct permanent porosity of the frameworks was established by N2 adsorption experiments. The Ni 2+ centers in the two frameworks locate in two different distorted octahedral coordination environments, which lead to the varying crystal color with the effect of diverse supramolecular packing of the crystal structures. Magnetic investigation revealed that the frameworks exhibit significant easy-axis magnetic anisotropy with the zero-field splitting parameter D  = -27.8 and −16.5 cm −1 for 1 and 2, respectively. However, no field-induced slow magnetic relaxation behaviors can be detected for 1 and 2 . The foregoing results highlight that simple organic molecule can be used for the preparation of supramolecular magnetic frameworks with permanent porosity and coordination polymers-based supramolecular porous frameworks can act as a platform for tunable porosity and magnetic properties.